2009
DOI: 10.1186/1471-2474-10-34
|View full text |Cite
|
Sign up to set email alerts
|

Classification of gluteal muscle contracture in children and outcome of different treatments

Abstract: Background: Gluteal muscle contracture (GMC) is a clinical syndrome due to multiple etiologies in which hip movements may be severely limited. The aim of this study was to propose a detailed classification of GMC and evaluate the statistical association between outcomes of different management and patient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(95 citation statements)
references
References 13 publications
(14 reference statements)
2
89
0
4
Order By: Relevance
“…Numerous authors believe GMC is secondary to repeated intramuscular injections, regardless of the type of medication injected into the buttocks [2,6,8,9,14] and/or a constitutional fibrogenic diathesis [2,7]. GMC is characterized by variable degrees of muscle atrophy and intramuscular fibrosis of the gluteus maximus muscle, which leads to restriction of internal rotation, adduction, and flexion of the affected hips.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous authors believe GMC is secondary to repeated intramuscular injections, regardless of the type of medication injected into the buttocks [2,6,8,9,14] and/or a constitutional fibrogenic diathesis [2,7]. GMC is characterized by variable degrees of muscle atrophy and intramuscular fibrosis of the gluteus maximus muscle, which leads to restriction of internal rotation, adduction, and flexion of the affected hips.…”
Section: Discussionmentioning
confidence: 99%
“…Although in the past, the diagnosis of GMC usually was derived from the history and physical examination, additional objective imaging studies are indicated not only for military certification but also for detailed evaluation of disease extent, degrees of muscle atrophy, and preoperative planning [2]. Operative release of fibrotic tissue with surgical division, resection [2,14], or radiofrequency energy [6] effectively restores reasonably normal squatting in patients with severe GMC; nonoperative management such as passive stretching is recommended as a primary treatment for mild GMC [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Несмотря на малое количество публикаций в отечественной научной печати [1], диагности-ка и клиника данной и схожей с ней патологии достаточно подробно описана в зарубежной ли-тературе [4][5][6][7]. По свидетельству ряда авторов [4,7], она встречается в США, Франции, Италии, Польше, Испании, Индии, но больше всего в Ки-тае.…”
Section: результат и обсуждениеunclassified
“…В русскоязычной литературе это заболевание обозначается как идиопатическая разгибатель-но-отводящая контрактура тазобедренного су-става или идиопатическая контрактура большой ягодичной мышцы [1,2], врожденная контрак-тура сухожилий больших ягодичных мышц [3]. В англо язычной литературе чаще встречается термин «врожденная или идиопатическая кон-трактура больших ягодичных мышц» (gluteal muscle contracture, GMC) [4][5][6][7].…”
Section: Introductionunclassified